The “Law and Order” of Violence Against Native Women: A Native feminist Analysis of the Tribal Law and Order Act - Robertson, Kimberly (Decolonization: Indigeneity, Education & Society, 2016)
In this essay, I aim to engage the growing body of scholarship that employs Indigenous feminist theories to understand and mobilize against the sexual and gendered violence committed against Native peoples. To accomplish this, I construct a Native feminist analysis of the 2010 Tribal Law and Order Act. I posit that despite the overwhelmingly positive characterizations of the legislation as “historic” in its potential to address violence against Native women and reduce crime in Indian country, a Native feminist reading of the Tribal Law and Order Act illuminates the degree to which the Act emerges from, engages with, and advances settler colonial and heteropatriarchal logics that cause violence against Native women in the first place. I suggest that although the Act does contain measures that have the potential to alleviate the experience of violence in Native women’s lives, it also diminishes tribal sovereignty, perpetuates the ongoing encroachment of tribal jurisdiction, regulates the boundaries of Native identity, and limits our ability to envision and enact practices of decolonization.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé